The Commons dalam Perspektif Kewargaan: Studi Konflik Pengelolaan Wisata Alam Desa Bleberan Gunungkidul - Fatih Gama Abisono; Tridaya Rini; Agustinus Sakro (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2020)
Abstract: This study aims to examine the perspective of citizenship as a way to resolve conflicts in commons management in the natural tourism of Bleberan Village, Gunungkidul. This study departed from the reality of the challenge of strengthening the market in guiding village public life, including the commons. At the same time, the village faced a decline in the role of the state as a bulwark for the presence of a sustained commons interest in the form of redistribution of citizens' welfare. This research used qualitative approach with an instrumental case study strategy. Case studies were chosen with the aim of perfecting or building new knowledge. Data was collected by a combination of techniques including interviews, FGDs, observations, and documentation with informans like entrepreneur, tourism unit operator, village government, village-owned enterprises management, and residents. This study found that conflict management in the commons in Bleberan rooted in the formation of contestation citizenship but without adequate negotiation capacity. The communitarian social building of citizens is interconnected with defective liberal citizenship which leads to exclusion, inequality, and concentration of welfare. Meanwhile, the republican model has not been able to offset the dominance of both. Weak negotiating capacity for membership, rights, and burdens on how the commons should be managed resulted in unmanaged contestation. This article concludes that it is important to track citizenship formations as a basis for finding a road map for conflict resolution in managing the commons.Intisari: Kajian ini bertujuan menguji perspektif kewargaan sebagai cara mengurai konflik pengelolaan the commons berupa wisata alam di Desa Bleberan Gunungkidul. Kajian dilatarbelakangi tantangan menguatnya pasar dalam memandu kehidupan publik desa, termasuk the commons. Pada waktu yang sama, desa dihadapkan pada merosotnya peran negara sebagai benteng keberlangsungan commons interest berupa redistribusi kesejahteraan warga. Penelitian ini berjenis kualitatif dengan strategi studi kasus instrumental. Studi kasus dipilih dengan tujuan menyempurnakan atau merintis pengetahuan baru. Data dikumpulkan dengan kombinasi teknik wawancara, FGD, observasi, dan dokumentasi dengan narasumber pelaku usaha, pengelola wisata, pemerintah desa, pengurus BUMDesa, serta warga. Hasil kajian menemukan konflik pengelolaan the commons di Bleberan berakar dari formasi kewargaan yang kontestatif namun tanpa diimbangi kapasitas negosiasi secara memadai. Bangun sosial komunitarian warga berkelindan dengan kewargaan liberal yang cacat memunculkan eksklusi, ketidaksetaraan, dan pemusatan kesejahteraan. Sementara itu model republikan belum mampu tampil mengimbangi dominasi keduanya. Lemahnya kapasitas negosiasi atas keanggotaan, hak, dan beban tentang bagaimana the commons seharusnya dikelola berimplikasi pada kontestasi yang tidak terkelola. Artikel ini menyimpulkan pentingnya melacak formasi kewargaan sebagai basis menemukan peta jalan resolusi konflik pengelolaan the commons.